Examining the Role of Gamification and Multimedia Learning in Enhancing Educational Engagement - Kinjalben Chandulal Thakkar; Dr. Pavankumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study examines the impact of gamification and multimedia learning on student engagement and comprehension in educational settings. By analyzing survey data from 630 students across government and private schools, the research highlights the transformative potential of these digital tools. Gamification, through its use of game-like elements, fosters motivation and active participation, while multimedia learning simplifies complex concepts using visual and interactive methods. The findings reveal a significant correlation between technological resource availability and the effectiveness of these strategies, with private schools demonstrating better outcomes due to enhanced infrastructure. However, challenges such as resource disparities, inadequate teacher training, and design limitations hinder widespread adoption. The study concludes by emphasizing the need for strategic investments in technology and professional development to bridge gaps and maximize the benefits of digital tools. These insights contribute to understanding how digital innovations can enhance educational engagement and outcomes.
Keywords: gamification; multimedia learning; student engagement; digital tools; educational technology; resource availability; teacher training; learning outcomes